Microbial Biopolymers as an Alternative Construction Binder - Cho, Gye Chun; Chang, Ilhan; Im, Jooyoung (Microbial Polymers: Applications and Ecological Perspectives, 2021)
With an increasing need for civil infrastructures owing to increasing populations and growing concerns on climate change, the need for sustainable construction material has become ever more present. Worldwide sustainable development has led to various technologies and materials for various engineering practices. Among such developments, the use of biopolymers in the field of geotechnical engineering has shown great promise. Biopolymers are naturally derived organic polymers that have shown a significant engineering performance. As a new material with a low carbon footprint, the use of biopolymer as a sustainable material has been increasing in recent years. In this chapter, the engineering performances of biopolymers in geotechnical engineering practices, methods of implementation, and limitations and future prospects of this material will be investigated.
Keywords: Biopolymer; Biopolymer-based soil treatment (BPST); Gellan gum; Xanthan gum